Determination of degradation of radioactivity and its kinetics in aerobic composting - Ipek, U; Öbek, E; Akca, L; Arslan, EI; Hasar, H; Dogru, M; Baykara, O (Elsevier Sci Ltd, 2002)
In this study, the kinetics of disappearance of radioactivity in aerobic composting was investigated. For this put-pose, compost materials were prepared by mixing sugar beet wastes, wine factory wastes (grape wastes), straw and biological treatment sludge in different amounts. While alpha-radioactivity was not initially detected in all composting materials, the composting materials had some beta-radioactivity. In the mixtures of sugar beet wastes -straw-biological treatment sludge (1), sugar beet wastes-wine factory wastes (grape wastes)-biological treatment sludge (II) and wine factory wastes (grape wastes)-biological treatment sludge (III), the beta-radioactivity reduced by 82%, 58%, 85% respectively of initial values after 52 d. The beta-radioactivity degradation in the composting process could be represented by first-order kinetics and reaction rate constants of mixtures of I, II and III were k = 0.0693 d (1) (R-2 = 0.84), k = 0.0453 d(-1) (R-2 = 0.98), k = 0.0234 d(-1) (R-2 = 0.97), respectively. (C) 2002 Elsevier Science Ltd. All rights reserved.
Keywords: aerobic composting; sugar beet wastes; wine factory wastes; radioactive degradation; kinetic